Characterization Of Rainwater From Rainwater Harvesting In Relation To Its Usage For Human Consumption - Nor Isdayanti Saaid (School of Environmental Engineering, Universiti Malaysia Perlis, 2015)
For this project, the objectives are to study on the physicochemical parameters of collected rainwater from asbestos roof within 5, 10, 15, 20, and 25 minutes of the start of rainfall. To determine the appropriate 'first-flush' period (a duration from the start of rainfall to the point where the contaminants in the collected rainwater has reach acceptable level), for an asbestos roof.